TRENDS OF EARLY SYPHILIS IN BELGRADE IN THE PERIOD 2001-2020 - Bjekic, Milan; Begovic-Vuksanovic, Biljana; Grujicic, Sandra (HEALTH CARE, 2023)
Introduction/Aim: In the period 2010-2019, in the countries of the European Union, the incidence of syphilis increased by 209.8% in men and in women there was a slight increase. The increase of incidence was particularly noted in the population of men who have sex with men (MSM). The aim of this study was to determine the trend of early syphilis in Belgrade in the period 2001-2020.Methods: For the analysis of the epidemiological situation of syphilis in the area of Belgrade in the period 2001-2020, data from reports on infectious diseases, medical documentation, annual reports on the work related to the prevention, suppression and elimination of infectious diseases and the results of epidemiological and laboratory tests were used. Data on the number of inhabitants regarding gender and age for Belgrade were taken from the 2011 census, while estimates were used for the years between censuses. Based on the obtained data, raw, age-specific and incidence rates by gender were calculated for syphilis. In order to analyze the trends in incidence rates of syphilis for the period 2001-2020, as well as for the period 2011-2020, joinpoint regression analysis was used.Results: In the period 2001-2020, a total of 938 cases of syphilis were registered, while the highest incidence rate was registered in 2018 (8.1/100,000), and the lowest in 2008 (0.5/100,000). In the period 2001-2008, the incidence rate of syphilis decreased by 1.1% per year (p > 0.05), while in the period 2009-2020, there was a significant increase of 24.3% per year. In the population of men, a significant increase in the incidence rate by 20.7% per year was registered in the period 2011-2020, while in the population of women, this increase was 0.9% per year, and it was not significant. In the period 2011- 2020, the highest incidence rates were in men aged 30-39 years, and in women aged 20-29 years. In all age groups, the incidence rate was higher in men than in women, while the average ratio of affected men and women was 11.9.Conclusion: Syphilis is still a common sexually transmitted infection in Belgrade, and therefore, early diagnosis and therapy are needed, especially among the members of vulnerable groups for sexually transmitted infections, in order to prevent the spread of this disease and the emergence of complications. Since it is common among women in the reproductive period, antenatal screening for this infection can be recommended to all pregnant women, and especially to those at increased epidemiological risk
Keywords: syphilis, incidence, joinpoint regression analysis